2005
DOI: 10.1073/pnas.0506164102
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin domain activation via GATA-1 utilization of a small subset of dispersed GATA motifs within a broad chromosomal region

Abstract: Cis elements that mediate transcription factor binding are abundant within genomes, but the rules governing occupancy of such motifs in chromatin are not understood. The transcription factor GATA-1 that regulates red blood cell development binds with high affinity to GATA motifs, and initial studies suggest that these motifs are often unavailable for occupancy in chromatin. Whereas GATA-2 regulates the differentiation of all blood cell lineages via GATA motif binding, the specificity of GATA-2 chromatin occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
141
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(153 citation statements)
references
References 77 publications
12
141
0
Order By: Relevance
“…Based on the analysis of a number of different genes it has been suggested that enhancer elements serve as nucleation centers for the establishment of active chromatin in stem cells (30). For example, after induction of GATA-1, transcription factor complexes on the ␤-globin locus are assembled in a stepwise fashion and associate first with the upstream locus control region and only later with the promoter (14). The same is true with the VpreB1 and the 5 locus, where enhancer-but not promoter-bound transcription factor complexes early in development (29).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the analysis of a number of different genes it has been suggested that enhancer elements serve as nucleation centers for the establishment of active chromatin in stem cells (30). For example, after induction of GATA-1, transcription factor complexes on the ␤-globin locus are assembled in a stepwise fashion and associate first with the upstream locus control region and only later with the promoter (14). The same is true with the VpreB1 and the 5 locus, where enhancer-but not promoter-bound transcription factor complexes early in development (29).…”
Section: Discussionmentioning
confidence: 99%
“…GATA-1 can both activate and repress globin genes, but the study of this factor is complicated because of its involvement in activation and repression of many transcription factors involved in erythroid differentiation. In the mouse b-globin locus, GATA-1 binds the promoter of the b maj -gene and HS1-HS4 of the LCR (23)(24)(25). Binding of GATA-1 to the promoter and HS2, but not to HS3 and HS4, depends on the GATA-1 interacting partner FOG-1 (23,24).…”
Section: Gata-1 and Fog-1mentioning
confidence: 99%
“…In the mouse b-globin locus, GATA-1 binds the promoter of the b maj -gene and HS1-HS4 of the LCR (23)(24)(25). Binding of GATA-1 to the promoter and HS2, but not to HS3 and HS4, depends on the GATA-1 interacting partner FOG-1 (23,24). The interaction with FOG-1 is also a determining factor for the involvement of GATA-1 in different protein-complexes that can have activating or repressing functions during development (26).…”
Section: Gata-1 and Fog-1mentioning
confidence: 99%
“…GATA motifs are abundant in DNA and reside at most erythroid-specific genes (8,19). GATA-1 and GATA-2 occupy a small subset of the conserved GATA motifs at the ␤-globin locus with qualitatively similar patterns (13,14). Sites can differ in apparent affinities, as ␤major promoter occupancy requires a greater activity͞level of an estrogen receptor (ER) ligand binding domain fusion to GATA-1 (ER-GATA-1) vs. the locus control region (13).…”
mentioning
confidence: 99%
“…GATA factors engage DNA and coregulators via a dual zinc finger domain (8), and other regions modulate activity (9,10). GATA-1 increases histone acetylation, dimethylation of histone H3 at lysine 4 (11)(12)(13), and RNA polymerase II recruitment (14) and induces higher-order chromatin changes (15).…”
mentioning
confidence: 99%